Characterisation of lossy low dielectric constant soda lime silica-high density polyethylene composites for microwave application - Meli, Abubakar Dantani (2019)
Composites material of low dielectric constant and high loss factor for microwave absorbing application are much needed. Composites materials of low dielectric constant and high loss factor, reflect electromagnetic waves less and absorb more. Composites of these characteristics can be use for security protection and to curb the menace of electromagnetic interference (EMI) pollution arising from the increasing number of the telecommunication users through mobile telephones, local area networks, wide area networks and radars systems. Generally microwave absorbing composites comprises of filler material in a host matrix. These fillers comprises of an element or more that carry out most of the absorption. Absorbing materials are applied in range of applications to remove the unrequired radiation that may affect an operation system. This research presents characterisation of lossy low dielectric constant soda lime silica-high density polyethylene (SLS-HDPE) composites for microwave absorbing application. The total mass of each blended composite was 25 g and contained 63 μm size SLS glass. The Brabender Plastograph EC blending machine was used to blend the composites at a speed rotor of 50 rpm for 10 minutes. Brabender was set at 170 °C of heating temperature which was chosen to restrict the flow of matrix HDPE whose melting point is 160 oC. SLS glass was chosen for this study because it is a solid waste output from milling process which is broadly and readily available. SLS glass shows a better mechanical properties in comparison to other glass. SLS glass and HDPE are biodegradable and both have low density unlike many other manufacturing materials. Different percentage of filler were used and blended to produce SLS-HDPE composites to give different absorbing properties in the HDPE matrix. The structural crystallinity of the composites was characterised via X-ray diffraction (XRD) machine. Theoretical calculations of the reflection and transmission coefficients of placed samples inside a rectangular waveguide and the placed samples on top of an open microstrip were simulated by using the Finite Element Method (FEM) in connection to COMSOL software. The measurement of the reflection and transmission coefficients, and also the dielectric properties, was carried out using the PNA (N5227) Network Analyzer for both rectangular waveguide and microstrip under room temperature for frequencies ranges 8 GHz to 12 GHz. Investigative analysis between the calculated and measured scattering parameters was also carried out. The permittivity complex of the composites was found to be mixing ratio dependent between SLS-HDPE. At X-band frequency 10 GHz, the real permittivity of SLSHDPE composites which is the dielectric constant was found to be between 2.44 to 2.91 respectively, while the imaginary permittivity which is the loss factor values were found to be from 0.05 to 0.17. The dielectric constant and loss factor of the composites can be predicted using the regression equations by putting the fractional values of the fillers composition. Both the dielectric constant and dielectric loss of the SLS-HDPE composites increased with increased in SLS fillers percentages. Thus, these, could result to obtain lower transmission coefficient |S21| and higher values of the magnitude of the reflection coefficient |S11| by the impedance matching theory. However, the obtained results from the scattering parameters was further used to determine the absorption loss of different SLS-HDPE percentages of samples composites. Lastly, investigation of the effect of different SLS filler percentages on the electric field was carried out by observing the pattern of electric field distribution of the samples of SLSHDPE composites placed in a rectangular waveguide technique. Electric field distribution via FEM showed that the higher the SLS fillers, the lower the transmittance of the field distribution across the sample from the input port to the output port of the rectangular waveguide. Observation showed a reduction in field strength as SLS fillers increases confirming the results obtained for the complex permittivity of the composites are ԑ'= 2.44 for 10%SLS, 2.55 for 20%SLS, 2.65 for 30%SLS, 2.83 for 40%SLS and 2.91 for 50%SLS respectively while the loss factor values are ԑ"=0.05 for 10%SLS, 0.08 for 20%SLS, 0.10 for 30%SLS, 0.15 for 40%SLS and 0.17 for 50%SLS where the highest permittivity measured ԑ'= 2.91 and ԑ"=0.17 were for the fillers of 50% SLS composites further addition of SLS filler will result to the flexibility and increase the absorption which can generate more heat in the composites and eventually the composites will breakup. The 50%SLS composites shows better thermal and electrical properties, higher dielectric constant, higher loss factor and higher loss tangent. The 50%SLS composites has the highest absorbing properties, hence it is the best for microwave absorbing application.